Soundscape Preference of Urban Residents in China in the Post-pandemic Era - Liu, Jinxuan; Xu, Jian; Wu, Zhicai; Cheng, Yuru; Gou, Yuxin; Ridolfo, Jesse (Frontiers in Psychology, 2021)
The purpose of this study is to explore the impact of the coronavirus pandemic on soundscape preference in public landscapes. This paper used the subjective evaluation method to conduct an online questionnaire in 29 Chinese provinces which experienced severe pandemic caseloads and collected 860 valid responses. The results revealed the changes and characteristics of people's preference for public landscape and soundscape due to pandemic prevention requirements and psychological pressure and analyzed the correlation and reasons between different landscape preferences and soundscape preferences. This paper explores the preferences of people with additional attributes for landscape and sound perception, examines the potential benefits of the soundscape to vulnerable groups under the pandemic situation—especially the impact of wearing masks and vaccination on landscape audio-visual perception—and puts forward some suggestions for public and acoustic landscape design in the post-pandemic era.